1994
DOI: 10.3177/jnsv.40.181
|View full text |Cite
|
Sign up to set email alerts
|

Biotin Production by Bifidobacteria.

Abstract: SummaryBiotin production and the growth of the strains of Bifido bacterium adolescentis, B. bifidum, B. breve, B, infantis, and B. longum were studied. These five strains showed heavy growth on BL medium. But when yeast extract medium (carbon source, glucose) was used, the extent of their growth was significantly decreased, one-half or less than that of the growth on BL medium. B. bifidum grew well on yeast extract medium containing oligosaccharides, such as isomaltooligosaccharide, and produced biotin extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 10 publications
(10 reference statements)
0
15
0
Order By: Relevance
“…For instance, the gut commensals Bifidobacterium and Lactobacillus can synthesize the B9 vitamin folate (Noda et al 1994;Pompei et al 2007;Strozzi and Mogna 2008;Kleerebezem and Vaughan 2009), which was shown to have a critical role in the maintenance of Treg cells in the small intestine (Kunisawa et al 2012). Vitamin B12 deficiency results in a decreased number of lymphocytes and suppressed NK cell activity (Tamura et al 1999).…”
Section: Retinoic Acid (Ra)mentioning
confidence: 99%
“…For instance, the gut commensals Bifidobacterium and Lactobacillus can synthesize the B9 vitamin folate (Noda et al 1994;Pompei et al 2007;Strozzi and Mogna 2008;Kleerebezem and Vaughan 2009), which was shown to have a critical role in the maintenance of Treg cells in the small intestine (Kunisawa et al 2012). Vitamin B12 deficiency results in a decreased number of lymphocytes and suppressed NK cell activity (Tamura et al 1999).…”
Section: Retinoic Acid (Ra)mentioning
confidence: 99%
“…Pollen is a rich source of Vitamin B but lactobacilli and bifidobacteria could produce at least Vitamin B7, B11 and B12 (Noda et al, 1994;Crittenden et al, 2003;Pompei et al, 2007;Santos et al, 2008) and…”
Section: Sequence Lengths (And % Similarity) **mentioning
confidence: 99%
“…Their physiological activity is thought to exert a range of beneficial effects on host health, such as protection against potentially pathogenic bacteria (Bernet et al 1993;Gibson and Wang 1994;Fujiwara et al 1999), reduction of serum cholesterol levels (Tahri et al 1995), vitamin production (Noda et al 1994) and enhancement of immune response (Kado-Oka et al 1991).…”
Section: Introductionmentioning
confidence: 98%